Implementing Cisco UCS solutions : a hands-on guide to deploy, manage, troubleshoot and automate Cisco UCS solutions in the data center /: a hands-on guide to deploy, manage, troubleshoot and automate Cisco UCS solutions in the data center. (2017) - Modi, Anuj; Nadeem, Farhan Ahmed; Sarkar, Prasenjit
No abstract available